Implementation of the Minister of Home Affairs Regulation Number 70 of 2019 regarding the Regional Government Information System in Pangkalpinang City, Bangka Belitung Province - Putra, Fajar Dwi; Simangunsong, Fernandes (Journal of Research in Social Science and Humanities, 2022)
This study aims to identify and analyze the implementation of the Minister of Home Affairs Regulation Number 70 of 2019 concerning Regional Government Information Systems, to identify and analyze the Determinants of the Minister of Home Affairs Regulation Number 70 of 2019 concerning Regional Government Information Systems. , knowing and analyzing efforts to overcome inhibiting factors in the implementation of the Minister of Home Affairs Regulation Number 70 of 2019 concerning Regional Government Information Systems in Pangkalpinang City, Bangka Belitung Province. This study uses the theory of implementation and determinants of policy implementation put forward by Muchlis Hamdi as an analytical knife that contains 3 (three) dimensions of policy implementation consisting of productivity, linearity, and efficiency, while the determinants of policy implementation contain 5 (five) factors influencing the success of policy implementation consisting of policy substance, implementing task behavior, network interaction, target group participation, and resources. The research method in this research is descriptive qualitative research with an inductive approach. Data collection techniques through interviews, observation, and documentation. The informants in this research are the Mayor of Pangkalpinang, DPRD of Pangkalpinang City, Secretary of the City of Pangkalpinang, Head of the Regional Development Planning and Research Agency, Head of Planning for Control and Evaluation of Regional Development, Head of Data and Information Section, Head of Regional Finance Agency, Head of Budget Division, and Head of Regional Financial Information Management Section. Data analysis techniques used include data reduction, data presentation and drawing conclusions. The results of this study indicate that the implementation of the Minister of Home Affairs Regulation Number 70 of 2019 concerning Regional Government Information Systems in Pangkalpinang City, Bangka Belitung Province has not been productive, not linear and not efficient. Determinants of the implementation of the Minister of Home Affairs Regulation Number 70 of 2019 concerning Regional Government Information Systems in Pangkalpinang City, Bangka Belitung Province, consist of two factors that most influence the success of implementation, namely, the interaction of networks and resources. Efforts were made to overcome the inhibiting factors, namely to return to the old system (SIMDA) to carry out the stages that were hampered in the local government information system in Pangkalpinang City.